Asymptotic investigation of probability characteristics of a generalized one-line system - Ivnitski, V. A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. А. Ивницкий, Асимптотическое исследование вероятностных характеристик обобщенной однолинейной системыV. A. Ivnickis, Apibendrintos vienos linijos sistemos tikimybių charakteristikų asimptotinis tyrimas